Predictors of in-hospital mortality in patients requiring transfer to the medical intensive care unit - Jibril, Huzefa; Muhammad Azhar; Arshad, Ainan; Awan, Safia; Syed Ahsan Ali; Muhammed Tariq (Journal of the Pakistan Medical Association, 2025)
Objective: To identify the factors associated with higher odds of in-hospital mortality among inpatients requiring transfer to the medical intensive care unit. Method: The retrospective audit was conducted from April 1 to September 30, 2023, at The Aga Khan University Hospital, Karachi, Pakistan and comprised data from January 1, 2018, to December 31, 2022, of patients initially admitted to the general ward or high dependency unit in the Department of Medicine who required transfer to the medical intensive care unit during hospitalisation. Data was analysed using SPSS 23. Results: Of the 601 patients with mean age 53.6±17.4 years, 373(62.1%) were males. Overall, 321(53.6%) of the patients expired while in the hospital. Patients whose transfer to the intensive care unit was initiated within 48 hours of admission had lower in-hospital mortality compared to those whose transfer was initiated beyond 48 hours of admission (p=0.004). Patients with a history of autoimmune disease or malignancy as co-morbid conditions, or a primary discharge diagnosis of sepsis had higher odds of in-hospital mortality (p<0.05). Conclusions: In-hospital mortality in patients requiring transfer to the intensive care unit was found to be very high. Early transfer to intensive care unit could lead to improved survival rate. Key Words: Critical care, Hospital medicine, Clinical deterioration, Sepsis, Autoimmune diseases.